Dynamic Programming Analysis for Measuring the Optimization of the Manpower per Shift PT. XYZ - Ida Rinjani; Sutrisno Sutrisno; Billy Nugraha (Jurnal Serambi Engineering, 2021)
The problems that occur in the company is the production system make to order, for example PT. XYZ. Unknown certainty the amount of the order lenses will be produced. So it is not known how labor should be allocated to each shift. Then used the approach of dynamic programming to optimize the number of workers per shift in the PT. XYZ. This study aims to determine the analysis of the dynamic programming optimization to allocate the amount of labor per shift to be effective. The type of research data is primary data obtained through direct observation in PT. XYZ. The results of the research based on the calculation of the forward recursive dynamic programming: shift 1 = 105 people, shift 2 = 104 people and shift 3 = 104 people. While the solution of the optimal allocation of labor for each shift based on the calculation of the backward recursive dynamic programming: shift 1 = 105 people, shift 2 = 104 people and Shift 3 = 104 people. Then the PT. XYZ should allocate 313 workers, so that the allocation of labor to each shift is optimal according to the order received